Primary lymphoma of the lacrimal sac: an EORTC ophthalmic oncology task force study. Issue 8 (3rd May 2006) - Sjö, L D; Ralfkiaer, E; Juhl, B R; Prause, J U; Kivelä, T; Auw-Haedrich, C; Bacin, F; Carrera, M; Coupland, S E; Delbosc, B; Ducrey, N; Kantelip, B; et al.
Abstract : Aim: To define the clinical and histopathological characteristics of primary lacrimal sac lymphoma in a predominantly white population. Methods: Specimens of lacrimal sac lymphoma and follow up data were solicited from members of the Ophthalmic Oncology Task Force of the European Organization for Research and Treatment of Cancer (EORTC) and the European Ophthalmic Pathology Society (EOPS). Specimens were stained with haematoxylin and eosin and an immunohistochemical panel against leucocyte antigens was applied. Diagnosis was reached by consensus of five experienced pathologists according to the World Health Organization classification system. The histopathological findings were correlated with the clinical data. Results: Of 15 primary lacrimal sac lymphomas, five (33%) were diffuse large B cell lymphoma (DLBCL), five (33%) were extranodal marginal zone B cell lymphoma of mucosa associated lymphoid tissue (MALT lymphoma), three were classified as "transitional MALT lymphoma, " being in transition from MALT lymphoma to DLBCL, and two were unclassified B cell lymphomas. Nine of the patients were female, and the median age at the time of diagnosis was 71 years (range 45–95 years). The most frequent presenting symptoms were epiphora (85%), swelling in the region of the lacrimal sac (79%), and dacryocystitis (21%). All but one patient presented in stage I. Systemic spread occurred in three of nine patients (33%). The 5 year overall survival was 65%. Conclusions: DLBCL and MALT lymphoma are equally common in the lacrimal sac in contrast with the remaining periorbital and/or orbital region where MALT lymphoma predominates.